New Detonating Compositions from Ammonium Dinitramide. Issue 5 (1st March 2021) - Comet, Marc; Schwartz, Cédric; Schnell, Fabien; Oudot, Franck; Lallemand, Bastien; Spitzer, Denis
Abstract: This article reports on a new family of detonating compositions in which ammonium dinitramide (ADN) is used as an explosive oxidizer, and red phosphorus (Pr ) or titanium hydride (TiH2 ) as fuels. At optimized ADN/fuel ratios, these compositions have typical explosion heats higher than 7 kJ/g, detonation velocities in 3 mm diameter tubes ranging from 1.2 to 2.0 km/s at ∼40 % of their theoretical maximum density, with a run to detonation distance between 20 and 40 mm. Both compositions are insensitive to electrostatic discharge, but are very sensitive to impact and friction, ADN/Pr mixtures being the most sensitive to these stress. The shockwave released by the reaction of these materials, efficiently initiates the detonation of high explosives such as pentaerythritol tetranitrate (PETN) or hexogen (RDX). In view of these characteristics, ADN‐based detonating compositions must be considered as "green" substitutes for primary explosives containing heavy metals. Abstract :